The Quest for Relics: Massive compact galaxies in the local Universe. Issue Volume 15:Issue S359(2020) (March 2019) - Lohmann, F. S.; Schnorr-Müller, A.; Trevisan, M.; Riffel, R.; Mallmann, N.; Chies-Santos, Ana L.; Furlanetto, C.
Abstract: Observations at high redshift reveal that a population of massive, quiescent galaxies (called red nuggets) already existed 10 Gyr ago. These objects undergo a significant size evolution over time, likely due to minor mergers. In this work we present an analysis of local massive compact galaxies to assess if their properties are consistent with what is expected for unevolved red nuggets (relic galaxies). Using integral field spectroscopy (IFS) data from the MaNGA survey from the Sloan Digital Sky Survey (SDSS), we characterized the kinematics and properties of stellar populations of massive compact galaxies, and find that these objects exhibit, on average, a higher rotational support than a control sample of average sized early-type galaxies. This is in agreement with a scenario in which these objects have a quiet accretion history, rendering them candidates for relic galaxies.